Removal of Methylene Blue from Aqueous Solution by Coffee Residues - Walaikorn Nitayaphat" (Science Faculty of Chiang Mai University, 2019)
The coffee residues, food industrial solid wastes, were used as low-cost adsorbent for the removal of methylene blue (MB) dye from aqueous solution. The experiments were performed under various conditions including contact time, solution pH, and adsorbent dose. The equilibrium time of MB adsorption was found to be 18 min. The maximum MB removal of 100% was obtained at initial pH 11 for an adsorbent dose of 1.0 g. The equilibrium time decreased with the increasing adsorbent dosage. The adsorption isotherm of coffee residues agreed well with the Langmuir model. The maximum adsorption capacity of coffee residues was 4.68 mg/g. The results demonstrated that the coffee residues are very effective in the removal of MB from aqueous solution and simple with low-cost.